Compulsion in Religion : Saddam Hussein, Islam, and The Roots of Insurgencies in Iraq - Helfont, Samuel (New York Oxford University Press, 2018)
'Compulsion in Religion' relies on extensive research with Ba'thist archives to investigate the roots of the religious insurgencies that erupted in Iraq following the American-led invasion in 2003.
Include Index
Keywords: Politics and government -- Islam and politics -- Islam and state